Penyelesaian Sistem Persamaan Linear (SPL) Dengan Dekomposisi QR - Shelvia Mandasari; Muhammad Subhan; Meira Parma Dewi (UNIVERSITAS NEGERI PADANG, 2014)
Abstract – QR decomposition is a numerical method to solves a System Linear Equations with n equations and n variables. This decomposition obtained by Gram Schimdt process and inner product space. From that method make an algorithm, that has been made a computer program to solve that System Linear Equations with n equations and n variables. The solution that obtained by this decomposition more accurate with small errors because this method only use two process so this decomposition more effective than that other numerical method. Keywords – Inner Product Space, Gram Schmidt Process, QR Decomposition